Kajian Tipologi Yunus di Perut Ikan dan Yesus di Perut Bumi sebagai Antitipe - Setiawan, Markus; Sunyono, Jawa Agriani; Rimun, Robinson; Purba, Jhon Leonardo Presley (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: The prophet Jonah is a typology of Jesus Christ himself as Jesus revealed to the Pharisees. Therefore there are some similarities between Jonah and Jesus but there are also differences where Jesus is the antitype of Jonah. Through a descriptive qualitative approach with a literature study method, this paper aims to study the typology of the event that Jonah stayed in the belly of a fish for three days as a type in the Old Testament which describes the event of the fulfillment of the prophecy of the redemption of Jesus Christ as an antitype in the New Testament. The conclusion of this study is that Jonah was in the belly of a huge fish for three days, which is a picture of Jesus to state the events of His death for three days in the heart of the earth. From the perspective of language equivalent Yunus is a typology that functions as an antitype to Jesus, where Jonah did not actually die physically but Jesus actually died physically and then came back to life, Yunus is a prophet while Jesus is the Son of God himself who has more authority from Jonah, Jonah's proclamation of God's salvation to the inhabitants of Nineveh occurred only once while Jesus Christ's preaching of salvation for mankind occurred until now and in the future, Jonah is not like Jesus because Jonah fled from God's calling and work, while Jesus from the beginning accepted God's mission for the salvation of mankind. But there are also similarities in the revelation of salvation, where through Jonah salvation was revealed to the repentant people of Nineveh and through Jesus salvation was revealed to all repentant mankind.Abstrak: Nabi Yunus merupakan tipologi dari Yesus Kristus sendiri sebagaimana yang dinyatakan Yesus kepada orang-orang Farisi. Karenanya terdapat beberapa kesamaan antara Yunus dengan Yesus namun terdapat juga perbedaan dimana Yesus menjadi antitipe dari Yunus. Melalui pendekatan kualitatif desktiptif dengan metode studi literature, paper bertujuan melakukan kajian tipologi peristiwa Yunus tinggal dalam perut ikan selama tiga hari sebagai tipe dalam Perjanjian Lama yang menggambarkan peristiwa penggenapan nubuatan akan karya penebusan Yesus Kristus sebagai antitipe di dalam Perjanjian Baru. Kesimpulan penelitian ini adalah Yunus berada dalam perut ikan besar selama tiga hari merupakan gambaran Yesus untuk menyatakan peristiwa kematianNya selama tiga hari di perut bumi. Dari perspektif language equivalent Yunus merupakan tipologi yang berfungsi sebagai antitipe terhadap Yesus, dimana Yunus tidak benar-benar mati secara fisik tapi Yesus benar-benar mati secara fisik dan kemudian hidup kembali, Yunus adalah seorang nabi sedangkan Yesus adalah Anak Allah sendiri yang memiliki otoritas lebih dari Yunus, pemberitaan Yunus akan keselamatan Tuhan kepada penduduk Niniwe terjadi hanya sekali sedangkan pemberitaan Yesus Kristus akan keselamatan bagi umat manusia terjadi hingga saat ini dan yang akan datang, Yunus tidak sama seperti Yesus karena Yunus melarikan diri dari panggilan dan pekerjaan Allah, sedangkan Yesus sejak awal menerima tugas misi Allah untuk keselamatan manusia. Namun terdapat juga kesamaan dalam penyataan keselamatan, dimana melalui Yunus keselamatan dinyatakan kepada penduduk Niniwe yang bertobat dan melalui Yesus keselamatan dinyatakan kepada seluruh umat manusia yang bertobat.